VALIDITY, RELIABILITY, AND DIAGNOSTIC PERFORMANCE OF GERIATRIC-8 AS A SCREENING TOOL FOR ABNORMAL COMPREHENSIVE GERIATRIC ASSESSMENT - Dibyantari, Ridzqie; Sari, Nina Kemala; Wahyudi, Edy Rizal; Muhadi; Rizka, Aulia; Mansjoer, Arif; Sutandyo, Noorwati (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2026)
The Geriatric Patient Plenary Assessment (P3G) is useful in the management of the elderly, but it is time-consuming, so screening instruments such as the Geriatric 8 (G8) have been developed. Initially designed for cancer patients, the G8 has also been shown to be valid in non-cancer elderly patients, but there have been no studies in Indonesia. This cross-sectional study (August 2023–March 2024) at the Geriatrics Clinic of Cipto Mangunkusumo National Hospital involved 80 subjects who underwent P3G and G8. An abnormal P3G was defined as impaired in ≥1 domain (ADL <20, IADL <8, MNA <24, MoCA-INA <26, or GDS >4). The results showed strong reliability (inter-rater kappa 1; intra-rater 0.904; ICC 0.77–1; Cronbach's α 0.697). The G8 had a sensitivity of 70.27% and a specificity of 83.33%, with an AUC of 0.846 (p<0.005). These findings demonstrate good diagnostic performance in identifying elderly individuals requiring a complete P3G. It is concluded that the G8 is valid and reliable as a screening tool for elderly individuals in the general Indonesian population, with good specificity.